2019
DOI: 10.21203/rs.2.13975/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primary caregivers perceptions  of the role of fathers in the provision of nutritional care in a resource constrained environment in Cape Town, South Africa

Abstract: Background : The role of fathers has traditionally been defined as a breadwinner or provider, with men generally having lower levels of engagement in childcare tasks, especially with young children. The involvement of fathers has important consequences for child well-being, especially with regards to issues of diet/nutrition, exercise, play, and parenting behaviours. This paper seeks to explore the perceptions and limitations that primary caregivers have on fathers’ provision of care in a resource constrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Other studies display how the quality, not necessarily the quantity, of interactions with a nonresident father is more important to a child's overall health when compared to children growing up with resident fathers 26 . In Cape Town, South Africa, an interview study was performed that showed a cascading effect of poverty influenced by inconsistent parenting that may lead to undernourishment and poor emotional consideration, especially from the father 27 . Brown et al found a lack of financial stability from the nonresident father, due to his irregular presence, was associated with dietary needs of the family not being met and being replaced with high fat and high sugar foods.…”
Section: Rct = Randomized Controlled Trialmentioning
confidence: 99%
“…Other studies display how the quality, not necessarily the quantity, of interactions with a nonresident father is more important to a child's overall health when compared to children growing up with resident fathers 26 . In Cape Town, South Africa, an interview study was performed that showed a cascading effect of poverty influenced by inconsistent parenting that may lead to undernourishment and poor emotional consideration, especially from the father 27 . Brown et al found a lack of financial stability from the nonresident father, due to his irregular presence, was associated with dietary needs of the family not being met and being replaced with high fat and high sugar foods.…”
Section: Rct = Randomized Controlled Trialmentioning
confidence: 99%